(Effect of the inclusion of whole wheat quinoa and amaranth flour in squid nuggets) - PALOMINO MANCILLA, KARINA (2022)
Nuggets are increasingly consumed, due to their easy preparation and unique qualities of taste, texture and overall appearance. The objective of this study was to research the effect of substituting wheat flour for quinoa flour and amaranth flour in the batter for the production of giant squid nuggets, fried at 180 °C for (30s) followed by 190 °C (10s). Inclusion levels were 10, 20 and 30% of quinoa flour and amaranth flour in the formulation of the batter. Apparent viscosity (AV) was measured using a RVDV-III Ultra RY82670 USA programmable Rheometer, the samples were adjusted to a temperature of 15 °C and measured using an RV5 spin at a penetration speed of 25 rpm, equipped with V3.2 Build 47-1 Rheocalc Software: Rheometer # 1, Windows version. By including integral quinoa flour and whole amaranth flour, the viscosity values ​​of the batter increased considerably to 3,856 VC, crust moisture to 31,31%, and pick-up to 39,24% of the crust; and on the contrary, it had an effect on decreasing the fat content to 21,90% of the bark. Wheat flour can be substituted up to 30% whole quinoa flour and whole amaranth flour in the batter formulation for squid nuggets, obtaining an increase in pick-up values, crust thickness and humidity; and a reduction in bark fat.